Smoke-Filled Room and Secret Garden of Politics: How Do Candidate Selection As Rational Choice in Local Head of Government Election? - Prianto, Andi Luhur (Universitas Pancasakti, 2025)
This study aims to analyze the candidate selection model in political parties, especially in the current electoral politics in Indonesia, which has not been adequately explained by previous studies. Candidate selection, distinct from political recruitment, is the process of selecting from a competitive group of candidates and frequently takes place behind closed doors, analogous to a “smoke-filled room” or a “secret garden of politics”. This practice raises issues of transparency, accountability and the dominance of party elites, who can overlook grassroots aspirations and candidate quality. This research uses a literature review method, exploring previous research and official documents to understand the concepts, practices and challenges of candidate selection. The findings show that the candidate selection mechanism often becomes an arena for internal party power struggles, far from democratic principles. This article also discusses democratic selection models based on the supply and demand perspectives of candidates and analyzes them through the lenses of new institutionalism and rational choice institutionalism. The rational choice institutionalism approach is considered relevant in explaining how individual and group interests influence the selection process. The study concludes that understanding these dynamics is important to promote a more democratic and accountable candidate selection system.